2021
DOI: 10.2147/ndt.s340771
|View full text |Cite
|
Sign up to set email alerts
|

Frontline Nurses’ Post-Traumatic Stress Disorder and Associated Predictive Factors During the Second Wave of COVID-19 in Central, Uganda

Abstract: Background Prior to the COVID-19 pandemic, the Ugandan healthcare system was already under severe strain due to a lack of human resources, poor working conditions, and poor management. At the center of these challenges are nurses, the backbone of the health system. This study investigated post-traumatic stress disorder and associated predictive factors during the second wave of COVID-19 among frontline nurses in the country. Participants and Methods This was a hospital-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
1
7
0
1
Order By: Relevance
“…Many reported that they were emotionally and physically exhausted (Akova et al, 2022; Bellanti et al, 2021; Brophy et al, 2021; Bruyneel, Gallani, et al, 2021; Butera et al, 2021; Wanninayake et al, 2022), which has impacted on their ability to be compassionate (Niu et al, 2022). Further, many healthcare workers have suffered from depression (Arslan et al, 2021; Cengiz et al, 2021; Duru, 2021), distress (Grailey et al, 2021; Naldi et al, 2021; Razu et al, 2021; Wanninayake et al, 2022) stress (Bergman et al, 2021; Cengiz et al, 2021; Fournier et al, 2022; Sethi et al, 2020; Zhan et al, 2020; Zhang, Xiang, & Alejok, 2021; Zhang, Zhang, et al, 2021), PTSD (Kabunga & Okalo, 2021) and anxiety (Daneshvar et al, 2022; Duru, 2021) due to high workloads. In addition, the incidence of healthcare worker burnout has also risen due to being exposed to chronic stress on a day‐to‐day basis over an extended period (Bellanti et al, 2021; Brophy et al, 2021; Bruyneel, Smith, et al, 2021; Butera et al, 2021; Gomez et al, 2020; Niu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Many reported that they were emotionally and physically exhausted (Akova et al, 2022; Bellanti et al, 2021; Brophy et al, 2021; Bruyneel, Gallani, et al, 2021; Butera et al, 2021; Wanninayake et al, 2022), which has impacted on their ability to be compassionate (Niu et al, 2022). Further, many healthcare workers have suffered from depression (Arslan et al, 2021; Cengiz et al, 2021; Duru, 2021), distress (Grailey et al, 2021; Naldi et al, 2021; Razu et al, 2021; Wanninayake et al, 2022) stress (Bergman et al, 2021; Cengiz et al, 2021; Fournier et al, 2022; Sethi et al, 2020; Zhan et al, 2020; Zhang, Xiang, & Alejok, 2021; Zhang, Zhang, et al, 2021), PTSD (Kabunga & Okalo, 2021) and anxiety (Daneshvar et al, 2022; Duru, 2021) due to high workloads. In addition, the incidence of healthcare worker burnout has also risen due to being exposed to chronic stress on a day‐to‐day basis over an extended period (Bellanti et al, 2021; Brophy et al, 2021; Bruyneel, Smith, et al, 2021; Butera et al, 2021; Gomez et al, 2020; Niu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Estudo aponta que alguns profissionais da enfermagem que perceberam riscos para a saúde acabaram deixando o emprego, no entanto, aqueles que permaneceram trabalhando na pandemia passaram por aumentos das cargas de trabalho e apresentaram maior propensão ao desenvolvimento de TEPT 23 .…”
Section: /14unclassified
“…A study points out that some Nursing professionals who perceived risks for their health eventually quit their job. However, those who continued to work during the pandemic experienced increased workload and were more prone to develop PTSD 23 .…”
Section: /14mentioning
confidence: 99%